Student Centre Approach in Teaching English for Specific Purposes Moodle-Based - Prasetya, Rizky Eka (English Education: Jurnal Tadris Bahasa Inggris, 2021)
The Indonesia higher education majority utilized the Language Management System (LMS) Moodle. The English Moodle-based teaching is a massive pedagogy shift due to pandemic. The study aimed to investigate and explore the technicality feature of teaching English, particularly the student-centered approach. The study was conducted in the qualitative approach experimental sequential research design. The substantive research instruments applied in the study comprised centered on questionnaires and interviews. The questionnaire was generated to investigate the lecturer used Moodle in their English language teaching. It is expected to discover the utilizing feature and adapting virtual class in LMS Moodle. The findings revealed that the system had an exclusive feature to accommodate student-centered teaching, yet it was found that the lecturer's unfamiliarity implied the inadequacy of Moodle course feature